A HAZOP gap query approach for hazard assessment in multiproduct facilities. Issue 2 (14th September 2017) - Torres, James; Ashley, Nick
Abstract : Batch, multiproduct chemical processing facilities present special challenges for conducting thorough hazard assessments. New or improved methods are needed to perform quality hazard analyses while reducing time and resource demands on facility personnel. A technique has been developed to expand traditional hazard and operability (HAZOP) methodology to include additional parameters for process operational intent, chemicals, and affected upstream/downstream equipment. Integrated Layer of Protection Analysis (LOPA) is applied to assess existing or proposed Independent Protection Layers, and compare resulting mitigated risk to risk criteria limits. The HAZOP for each unit then becomes a baseline hazard assessment, to which subsequent processes can be compared, without having to repeat the full HAZOP for each new process. For new products, a process intent template is completed by selecting the chemicals and equipment to be used, as well as the unit operations and conditions for each step in a semibatch process. The unit HAZOP file is queried using programmed search logic to identify matching process intent/equipment/chemicals parameters that were considered during the base HAZOP. A condensed Process Hazard Review is conducted to review the results, ensure identified items are applicable to the proposed new process, and evaluate new items that were not previously covered under the base HAZOP. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 161–168, 2018